Hard work never hurt anyone: or did it? A review of occupational associations with soft tissue musculoskeletal disorders of the neck and upper limb. Issue 10 (14th September 2005) - Walker-Bone, K; Cooper, C
Abstract : Pain in the neck and upper limb is common and contributes considerably to absence from work due to sickness. Evidence suggest that prolonged abnormal posture and repetition contribute to such conditions. Psychosocial risk factors may also play a part in the aetiology of upper limb disorders.